Expression analysis of p50-associated COX-2 extragenic RNA and NF-Kappa B Interacting long non-coding RNA in multiple sclerosis patients - Zeinab Shirvani-Farsani; Mina Rezaei; Zahra Abedi Kichi; Mehrdad Behmanesh; Shirin Farivar (Journal of Pharmaceutical and Biomedical Analysis Open)
Inflammatory long non-coding RNAs (lncRNAs) including PACER (p50-associated COX-2 extragenic RNA) and NKILA (NF-Kappa B Interacting long non-coding RNA) and have recently emerged as essential regulators in immune and inflammation pathways in patients with multiple sclerosis (MS), which have possible worthiness as diagnostic, prognostic, and therapeutic targets. In the current study, we aimed to evaluate the expressions of PACER, NKILA lncRNAs, CTCF (CCCTC-binding factor), and NF-κB in the PBMC (peripheral blood mononuclear cells) from MS patients and control subjects. We detected the expression levels of PACER, CTCF, NKILA, and NF-kB using real-time PCR in 39 MS patients and 37 healthy controls. The findings show that the expression levels of PACER lncRNA and CTCF, but not NKILA lncRNA and NF-κB, have significantly decreased in MS patients compared to the controls, so they are probably involved in MS pathogenesis. Notably, the area under the ROC curve for PACER and CTCF was up to 0.80 and 0.68, respectively. Based on these observations, the PACER and CTCF had been shown to have the best efficiency in the discrimination of disease status between MS patients and healthy controls. A low expression level of CTCF was correlated with PACER lncRNA and NF-KB expression levels as well as some factors including disease duration, age, and EDSS. Altogether, these results demonstrate that PACER lncRNA and CTCF were potentially related to the MS risk. However, further functional investigations are required to conﬁrm the roles of these genes in the etiology of MS.